BIOCHEMICAL AND PATHOLOGICAL EFFECTS ON THE MALE RAT HEPATIC TISSUE AFTER EXPOSURE TO 900MHZ ELECTROMAGNETIC FIELD DURING ADOLESCENT PERIOD - İKİNCİ KELEŞ, Ayşe; EROL, Hüseyin Serkan; SAPMAZ, Tuğçe; MERCANTEPE, Tolga; KELEŞ, Gökhan; BİTERGE SÜT, Burcu; ODACİ, Ersan; HALICI, Mesut; POLAT, Sait (Ankara University, 2021)
The aim of this study was to employ biochemical analysis and histopathological techniques to investigate the effects of the application of a 900-megahertz electromagnetic field during adolescence on the rat liver. 24 male Sprague Dawley rats aged 21 days were randomly divided into electromagnetic field, sham and control groups. No procedure was performed on the control group rats. Electromagnetic field group rats were exposed to a 900-megahertz electromagnetic field in an electromagnetic field application cage (1 hours/day, every day for 25 days). The sham group rats were placed in the same electromagnetic field cage without exposure to electromagnetic field. At the end of the experiments, the livers were removed. The livers were used for histopathological evaluation (light, electron and immunofluorescence microscopy) and biochemical analyses. Biochemical analyses revealed increased lipid peroxidation and glutathione values while catalase and superoxide dismutase values were decreased in electromagnetic field group. Electron microscopy evaluations identified necrotic hepatocytes with numerous cytoplasmic and mitochondrial vacuoles in electromagnetic field group sections. We also observed an enlarged endoplasmic reticulum and loss of mitochondrial matrix, in addition to the presence of vacuoles. Also, loss of inner and outer mitochondrial membrane integrity was observed. Light microscopy evaluations revealed sinusoidal capillary dilatation and degeneration in hepatocytes with cytoplasmic swelling, vacuolar degeneration and pyknotic nuclei in electromagnetic field group sections. Deterioration in the integrity of the collagen fibers was also present around the vena centralis. Additionally, electromagnetic field had no effect on body weight. Therefore, we conclude that continuous 900-megahertz electromagnetic field treatment may cause changes in oxidative stress biomarkers and the morphology of the adolescent rat liver.
Keywords: Structural Biology; Yapısal Biyoloji; Adolescence; Electromagnetic field; Histopathology; Liver; Oxidative stress; 3. Good health